Hubungan Perilaku Merokok Sebelum Tidur Dengan Kejadian Insomnia Pada Remaja Laki-Laki Di Dusun Bolor Sembe Desa Rarang Batas Tahun 2019 - Junaidi, Mansur; Amrullah, Muhammad (Jurnal Kesehatan Qamarul Huda, 2020)
Smoking behavior is the behavior of respondents who describe smoking activities that can be seen from the stage of smoking behavior, smoking intensity, smoking time. Smoker in indonesia society trun out not only to adults, but also to adolescents. Smoking behavior of men and women is generally first done when entering adolescence. The prevalence of indonesia population aged 15 year and over who smoke every day is 28%. Nationally. Nicotine dependence cause a smoker to have to smoke cigarettes continuously and cause various effects on the body, one of which is insomnia. There is a relationship between smoking behavior before sleeping with the incidence of insomnia in teenage boys in bolor sembe village 2019. To know the relationship of smoking behavior before sleeping with the ocurrence of insomnia in teenage boys in bolor sembe village 2019. The research method used in this study is cerrelational analytic with cross sectional approach with a total sample of 63 people with total sampling technique of statistical test using chi-square. From 63 sample that were examined by research criteria, after doing a statistical test using chi-square, the p value or sig (2-tailed) = 0,03 was obtained. the results show that the p value < a significant (0,03 < 0,05). There is relationship but a sufficient relationship between smoking behavior before going to sleep with the incidence of insomnia in adolecent boys in bolor sembe village 2019.